2010
DOI: 10.1002/elps.201000361
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification and comparative analysis of asymmetrically arginine‐methylated proteins in immortalized, young and senescent cells

Abstract: Protein-arginine methylation is one of the modifications that yields mono and dimethyl (asymmetric or symmetric) arginine residues in proteins. Previously, we found that asymmetric arginine methylation is decreased proportionately with a decrease of cell proliferation potential of cells, and such arginine methylation is greatest in immortalized cells, followed by normal young cells, and lowest in replicatively senescent cells. Using an asymmetric dimethyl-arginine-specific antibody, we identified arginine-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Therefore, the age-related differences of PRMTs level and activities in female rat tissues including ovary and estrogen receptor-positive tissues may show a similar pattern with male rats and will be researched further. Previously, we observed a possible link between protein arginine methylation and cellular senescence in vitro (Lim et al 2008(Lim et al , 2010. We found a significant reduction in the expression and catalytic activity of all PRMTs tested (PRMT1, PRMT4, PRMT5, and PRMT6) in replicatively senescent cells relative to young cells.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Therefore, the age-related differences of PRMTs level and activities in female rat tissues including ovary and estrogen receptor-positive tissues may show a similar pattern with male rats and will be researched further. Previously, we observed a possible link between protein arginine methylation and cellular senescence in vitro (Lim et al 2008(Lim et al , 2010. We found a significant reduction in the expression and catalytic activity of all PRMTs tested (PRMT1, PRMT4, PRMT5, and PRMT6) in replicatively senescent cells relative to young cells.…”
Section: Discussionmentioning
confidence: 75%
“…However, our previous study identified other substrate proteins in the cellular senescence model. These include chaperone molecules and RNA-binding proteins (RBPs) like Cleavage stimulation factor 2 (CstF2), Heterogeneous nuclear ribonucleoprotein K (hnRNP K), and Chaperonin containing TCP1, subunit7 (CCT7) (Lim et al 2010). Therefore, many still remain to be determined for the role of arginine methylation in aging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disturbance of insulin secretion Koeck et al, 2009 S-nitrosylation Cysteine Cardioprotective effects Sun et al, 2007;Lin et al, 2009;Kohr et al, 2014 Cysteine 237 Mitochondrial stability and endothelial integrity Suliman et al, 2010;Huang et al, 2012 Citrullination Not defined Pro-apoptotic Lu et al, 2016 Methylation Lysine 490; Arginine Pro-proliferative Lim et al, 2008;Lim et al, 2010;Cao et al, 2013 Oxidation Not defined Response to cellular injury and cell migration Suh et al, 2004;Lin et al, 2016 Biotinylation Lysine Anti-oxidant effect Li et al, 2014 Ubiquitination Lysine 396 Regulation of stress-activated ubiquitin-proteasome pathway Leach et al, 2011;Tang et al, 2013; Marino Gammazza et al, 2017a…”
Section: O-glcnacylation N-glycosylation and Acetylationmentioning
confidence: 99%
“…Senescent fibroblasts showed low level of asymmetric arginine di-methylation of Hsp60 compared to low-passage fibroblasts. This means that arginine asymmetric di-methylation of Hsp60 is correlated with the proliferation potential of cells and might be useful as a marker of cellular senescence (Lim et al, 2008(Lim et al, , 2010.…”
Section: Citrullination and Methylationmentioning
confidence: 99%